Here she comes: women of convict criminology - Woodall, Denise (2024)
In response to Joanne Belknap’s 2014 presidential address in which she critiqued the white male dominance of Convict Criminology, formerly incarcerated women formed the group’s fi rst thematic panel on “Women of Convict Criminology” at the American Society of Criminology annual conference in 2016. This article reports the results of an analysis presented in the fi rst session that illustrates the invisibility of directly impacted women contributors to our knowledgebase and recaps the inspiration, courage, and empiricism that sparked the presence of a new, more diverse group of directly impacted people fi ghting for recognition and inclusion in knowledge construction within ‘malestream’ criminology. Ways of conceptualizing carceral status as one axis of oppressions and directions for the future of Convict Criminology are discussed.